Characteristics of dissolved pores and dissolution mechanism of zeolite-rich reservoirs in the Wuerhe Formation in Mahu area, Junggar Basin. Issue 1 (January 2022) - Li, Ji; Zhang, Wenjie; Xiang, Baoli; He, Dan; Yang, Shengchao; Wang, Jian; Li, Erting; Zhou, Ni; Sun, Funing; Hu, Wenxuan
The reservoir in the Wuerhe Formation in the Mahu Sag, northwestern Junggar Basin, China, exhibits complex dissolution and cementation related to zeolite. The source and mechanism of diagenetic fluids are crucial in studying the reservoir genesis. Thus we investigated the key reservoirs fluids related to the zeolite and discussed their significance in the zeolite-rich reservoir of the Permian Wuerhe Formation in the Mahu Sag. Based on thin sections and electron microscope observations of rock samples and analyses of physical properties, C-O isotopes, and major elements, it is found that the reservoir underwent mainly two stages of fluid-related dissolution and cementation processes, in which the hydrocarbon-bearing fluid played the primary role in forming the high-quality reservoir. Dissolution pores are the most important storage space, and zeolite cement is the most important dissolution mineral. The geochemical characteristics of zeolite and calcite cement indicate the presence of two diagenetic fluids. The iron-rich calcite and orange-red heulandite is related to early diagenetic fluids with high iron content and higher carbon isotope values, whereas the calcites, with high manganese content and lower carbon isotope values, are formed by late acidic organic diagenetic fluids related to oil and gas activities. The hydrocarbon-bearing fluids form different spatial diagenetic zones, including the dissolution zone, buffer zone, and cementation zone, and the dissolution zone near the oil source fault is the main site of zeolite dissolution. The late fluid has the characteristics of multi-stage activity, which makes the spatial zoning expand gradually, resulting in multiple superpositions of dissolution and cementation and increasing the complexity and heterogeneity of the reservoir diagenesis. This study expands the understandings of the dissolution activities of different fluids in zeolite-rich reservoirs and also has reference significance for dissolution activity of hydrocarbon fluid in other types of reservoirs.